STRATEGI PENGEMBANGAN INDUSTRI PENGOLAHAN SABUT KELAPA NASIONAL - A. H. Intan; E. Gumbira Sa'id; Imam Teguh Saptono (School of Business, Bogor Agricultural University (SB-IPB), 2004)
Empowerment of social economic resourceprograms must be able to conduct public economy dynamic which be based atvillage or country town. These programs must be able to achieve seven goals,such as rising public income and net export income; founding industrialstructure based on the strength of Small-Medium Enterprises; founding thefoundation of economic transition to industrial age by developing forces ofagribusiness and agroindustrial system; achieving global competitive advantageby increasing productivity, innovation, and effective technology dissemination;increasing quality product as well as the global quality standars; and creatingeconomic development to attain sustainability of high economics activity andperformance and keep sustainable quality environment.Coir processing industry is one of Indonesia isindustrial sub sector which was identified having the ability to achieve thesegoals. Several logical reasons are pointed out, such as that Indonesia has greatest coconut planted areas(about 3.76 Million hectares or 31.4 percent of coconut planted areas in theworld), so that Indonesiaget 24.4 percent of coconut production share in the world. Contrast with coirexport share, Indonesiahas only about 0.6 percent (595 MT) of the world export market share. Untilyear 2000, Indonesiause only about 0.06 potential resources of coir production. So that, TheNational Coir Industry has strategic position ang high prospect will be developedat the next time.This article discuss and describeseveral topics to support the Indonesian Coir Industry Development Program,such as mapping Coir Industrial Development Areas based on the potency ofcoconut production and plated area; economic of Industrial scales analysis,structure of industrial development system, feasibility study (financial andeconomic analysis), Analysis of Domestic Resources Cost, Domestic ResourcesCost Ratio and Affective Rate Protection, Finally, this article describe statedprocess of coir industry development strategy and stated strategyrecommendation to stakeholders.